2021
DOI: 10.1186/s12887-021-02522-5
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and predictive validity of the infant motor profile in infants at risk of neurodevelopmental disorders

Abstract: Background Preterm infants and infants with perinatal brain injury show a higher incidence of neurodevelopmental disorders (NDD). The Infant Motor Profile (IMP) is a clinical assessment which evaluates the complexity of early motor behaviour. More data are needed to confirm its predictive ability and concurrent validity with other common and valid assessments such as the Alberta Infant Motor Scale (AIMS) and Prechtl’s General Movement Assessment (GMA). The present study aims to evaluate the con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(40 reference statements)
1
9
0
1
Order By: Relevance
“…Yet, AHLS with stereotyped leg movements, i.e., the pattern that van Haastert et al described, was associated with a doubling of the risk of low IMP-variation scores. From other studies we know that lower scores on movement variation in infancy are associated with atypical neurodevelopmental outcome, including lower cognitive scores at later age [17][18][19][20]. Thus, our data support the notion that AHLS with stereotyped leg movements may be associated with lower cognitive scores at later age.…”
Section: Discussionsupporting
confidence: 87%
“…Yet, AHLS with stereotyped leg movements, i.e., the pattern that van Haastert et al described, was associated with a doubling of the risk of low IMP-variation scores. From other studies we know that lower scores on movement variation in infancy are associated with atypical neurodevelopmental outcome, including lower cognitive scores at later age [17][18][19][20]. Thus, our data support the notion that AHLS with stereotyped leg movements may be associated with lower cognitive scores at later age.…”
Section: Discussionsupporting
confidence: 87%
“…Two retrospective clinical studies addressed IMPs prediction of CP. They showed that low IMP scores predicted CP well, one study reported areas under the receiver-operating characteristic curves: 0.89-0.99 [109], the other a sensitivity of 93% and a specificity of 81% [110]. Low IMP scores also have been associated with lower IQ scores at preschool and school age [111,112].…”
Section: Motor Assessmentsmentioning
confidence: 99%
“…The prediction process is a most complicated task in various fields and applications that need to provide an appropriate set of data for further analysis. Sports data is a collection of relevant information and data that provide optimal details for various sports events [ 6 ]. Sports data contains details such as the infant's name, age, gender, height, weight, allergies, rashes, activities, and skills collected by performing a certain function.…”
Section: Introductionmentioning
confidence: 99%